Exposure to a Predator Scent Induces Chronic Behavioral Changes in Rats Previously Exposed to Low-level Blast: Implications for the Relationship of Blast-Related TBI to PTSD - Perez-Garcia, Georgina; Gama Sosa, Miguel A.; De Gasperi, Rita; Lashof-Sullivan, Margaret; Maudlin-Jeronimo, Eric; Stone, James R.; Haghighi, Fatemeh; Ahlers, Stephen T.; Elder, Gregory A. (Frontiers in Neurology, 2016)
Blast-related mild traumatic brain injury (mTBI) has been unfortunately common in veterans who served in the recent conflicts in Iraq and Afghanistan. The postconcussion syndrome associated with these mTBIs has frequently appeared in combination with post-traumatic stress disorder (PTSD). The presence of PTSD has complicated diagnosis since clinically PTSD and the postconcussion syndrome of mTBI have many overlapping symptoms. In particular establishing how much of the symptom complex can be attributed to the psychological trauma associated with PTSD in contrast to the physical injury of TBI has proven difficult. Indeed some have suggested that much of what is now being called blast-related postconcussion syndrome is better explained by PTSD. The relationship between the postconcussion syndrome of mTBI and PTSD is complex. Association of the two disorders might be viewed as additive effects of independent psychological and physical traumas suffered in a war zone. However we previously found that rats exposed to repetitive low-level blast exposure in the absence of a psychological stressor developed a variety of anxiety and PTSD-related behavioral traits that were present months following the last blast exposure. Here we show that a single predator scent challenge delivered 8 months after the last blast exposure induces chronic anxiety related changes in blast-exposed rats that are still present 45 days later. These observations suggest that in addition to independently inducing PTSD-related traits, blast exposure sensitizes the brain to react abnormally to a subsequent psychological stressor. These studies have implications for conceptualizing the relationship between blast-related mTBI and PTSD and suggest that blast-related mTBI in humans may predispose to the later development of PTSD in reaction to subsequent psychological stressors.